Economics for lawyers - Ippolito, Richard A. (Princeton University Press, 2005)
Whether dealing with contracts, tort actions, or government regulations, lawyers are more likely to be successful if they are conversant in economics. Economics for Lawyers provides the essential tools to understand the economic basis of law. Through rigorous analysis illustrated with simple graphs and a wide range of legal examples, Richard Ippolito focuses on a few key concepts and shows how they play out in numerous applications. There are everyday problems: What is the social cost of legislation enforcing below-market prices, minimum wages, milk regulation, and noncompetitive pricing? Why.